BLT Method for PI Controllers of Unstable Systems. Issue 4 (2nd October 2018) - Besta, Chandra Shekar; Chidambaram, Manickam
Abstract: The biggest log modulus tuning (BLT) method is extended to unstable systems. The method is modified to design (i) decentralized Proportional-Integral (PI) controllers and (ii) centralized PI controllers for two-input two-output (TITO) systems. A method is given to specify the value for The internal model controller using Tanttu and Lieslehto method is applied for centralized controller design. The detuning parameter ( F ) is selected for both the schemes (centralized controller and decentralized controller) to get the value of BLT as +12 dB. Simulation studies are carried out for two TITO systems to evaluate the performance of both the proposed schemes. The centralized controllers produce superior performances and decreased interactions over the decentralized PI controllers. The present method gives robust performances.